2021
DOI: 10.7150/ijbs.54858
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles and pancreatitis: mechanisms, status and perspectives

Abstract: Comprehensive reviews and large population-based cohort studies have played an important role in the diagnosis and treatment of pancreatitis and its sequelae. The incidence and mortality of pancreatitis have been reduced significantly due to substantial advancements in the pathophysiological mechanisms and clinically effective treatments. The study of extracellular vesicles (EVs) has the potential to identify cell-to-cell communication in diseases such as pancreatitis. Exosomes are a subset of EVs with an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 129 publications
0
17
0
Order By: Relevance
“…Recent studies suggest that extracellular miRs serve as ideal disease biomarkers in head and neck squamous cell carcinoma [ 131 ], inflammation [ 132 ], and pancreatitis [ 133 ]. These miRs can be detected in body fluids, such as blood [ 134 ], by applying a sensitive, cheap, and simple assay.…”
Section: Extracellular Mirs As Disease Biomarkersmentioning
confidence: 99%
“…Recent studies suggest that extracellular miRs serve as ideal disease biomarkers in head and neck squamous cell carcinoma [ 131 ], inflammation [ 132 ], and pancreatitis [ 133 ]. These miRs can be detected in body fluids, such as blood [ 134 ], by applying a sensitive, cheap, and simple assay.…”
Section: Extracellular Mirs As Disease Biomarkersmentioning
confidence: 99%
“…1 a). In a previous study, exosomal miRNAs were extracted and examined using microarrays; 30 miRNAs were found to be upregulated in AP [ 1 ]. Furthermore, the study demonstrated that pancreatic acinar cells regulate macrophage activation by secreting exosomes carrying miRNAs.…”
Section: Application Of Exosomes In the Diagnosis Of Pancreatic Diseasesmentioning
confidence: 99%
“…Pancreatic diseases, such as acute pancreatitis (AP), chronic pancreatitis (CP), pancreatic cancer (PaCa), and diabetes, form a large category of complex diseases with high incidence and mortality. The global mortality rates associated with AP and CP are 1.60 and 0.09 per 100 000 individuals per year, respectively [ 1 ]. AP is the fifth most common cause of death of patients in hospitals, with an incidence rate of 34 per 100 000 individuals per year globally [ 2 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon entering a cell, e.g., by endocytosis, late endosomes containing sEVs either fuse with lysosomes to recycle sEVs and their cargos, or release their content into the cytoplasm to trigger signaling pathways or transcriptional changes [ 21 ]. There is ample evidence that sEVs have vital functions in carcinogenesis and evolution of PDAC as well as in the pathogenesis of precancerous conditions of the pancreas, including pancreatitis or pancreatic fibrosis [ 49 , 50 ]. Indeed, sEVs were shown to promote the transformation of precancerous lesions, such as PanINs to PDAC.…”
Section: Overview: Small Extracellular Vesicles and Its Predominant Subgroup Exosomesmentioning
confidence: 99%